Nanocellulose effects on microRNA expression in human bronchial epithelial cells - Ventura, Célia (2022)
Nanocellulose is an innovative nanomaterial with physicochemical properties (high specific area, high tensile strength and stiffness, gas barrier properties, optical properties, and biodegradability) that give it potential for a wide variety of industrial (packaging, paper industry and others) and biomedical applications (regenerative medicine, wound healing, drug delivery systems and others).